FPGA implementation of closed‐loop compensation for LFMCW signal non‐linear distortions. Issue 2 (1st April 2019) - Qian, Rong; Jiang, Defu; Fu, Wei
Abstract : Linear‐frequency‐modulated continuous‐wave (LFMCW) radars with deramping technique have several advantages such as compact size, low cost, and easy implementation, compared to traditional pulse radars; however, the non‐linear distortions caused by analogue modules, particularly power amplifiers, may deteriorate the radar detection performance. To solve this problem, a digital closed‐loop compensation scheme for the LFMCW signal is proposed, which can compensate the LFMCW signal in real time, when the non‐linear distortions change with the working environment. The proposed compensation scheme improves the detection performance, noticeably. Considering the speed limitations of field programmable gate arrays (FPGAs), the proposed scheme is implemented in an FPGA at an intermediate‐frequency level, using a polyphase processing structure.